Palm Avenue (Pacific Novelty Co.)
On verso: One of the marvels of the Exposition is the transformation that has been made on the grounds under the direction of John McLaren, the frostless climate of San Francisco enabling plants and shrubbery and semi-tropical trees to attain the highest perfection.